Taghazzul in Iqbal and Faiz' Poems - Maimona Subhani (بازیافت, 2020)
ABSTRACT: Poem is known among important portions of poetry. It is necessary for poet to keep the beauty of poem with poetry's compassion and sensitivity. The subject of poem should not organize in such way that becomes harsh in listening. The arrangement of words should be made in a manner to portray its sense of beauty and compassion. There are few poets in Urdu literature who try to maintain the color of "Taghazul" in their poetry. In fact Taghazul is a term of poetry. Terms are the source of communication in different languages. The style, diction, cadence, imagination, elegancy, inflection and spontaneity in poetry are the elements which increase the beauty of ghazal. Taghazul is not a genre of poetry. In fact it came from the combination of painful emotions and desire. It is very important in taghazul to summarize the delicacy and expression of words. If we look at the history of Urdu poem, from the poets of Anjuman-e-Punjab to Halqa-Arbab-e-Zuaq there are many important names, but there are two names known as the pillar of Urdu poetry. These are "Iqbal" and "Faiz". Both poets had the status of pillar in Urdu poetry. Iqbal presented the color of taghazul in his poems beautifully. "Shikwa, Jwab-e-Shikwa, Khizar rah, Shama-o-Shair, Masjad Qurtaba and Saqi Nama are his very significant poems. Faiz didn't lost the line of taghazul he also continued this method. "Manzar, Tanhai, Raqeeb sy, Aa jao Africa, Mujh sy Pahli c Muhabat mary Mehbob na mang and Shishu ka koi Maseeha nhi" are Faiz's key poems. Iqbal was a philosopher and his poetry is vastly under this umbrella. And the poetry of Faiz consist the tension and emotions of public. Both poets belong to different eras and both OS gƒÑÔ;gE-[ºÔÒ»@gzZÔzŠgZ£Ô(Y2020cŠ@*ðÑ)37DkÊ^m‡^e try to follow different visible perception of poetry. They became similar at one specific point that is taghazul in their poems, and this would be admired in every era.